We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
585
1
avatar

Can you solve log sub base 2 (x+1) + log sub base 2 (x+7) =3 with steps showing how you get to the answer? I get to the log sub base 2 (x+1)(x+7) = 3 but I don't know where to go from there.

 Jul 9, 2015

Best Answer 

 #1
avatar+17777 
+5

log2(x + 1) + log2(x + 7)  =  3

log2[ (x + 1)(x + 7) ]  =  3

Simplifying the left side:

log2[ x2 + 8x + 7 ]  =  3

Write in exponential form:

x+ 8x + 7  =  23

x+ 8x + 7  =  8

x+ 8x - 1  =  0

Now, finish by using the quadratic formula (You will need to reject imaginary answers and any answer that is less than or equal to 0 (because that will create a log of a non-positive number, which is undefined).)

 Jul 10, 2015
 #1
avatar+17777 
+5
Best Answer

log2(x + 1) + log2(x + 7)  =  3

log2[ (x + 1)(x + 7) ]  =  3

Simplifying the left side:

log2[ x2 + 8x + 7 ]  =  3

Write in exponential form:

x+ 8x + 7  =  23

x+ 8x + 7  =  8

x+ 8x - 1  =  0

Now, finish by using the quadratic formula (You will need to reject imaginary answers and any answer that is less than or equal to 0 (because that will create a log of a non-positive number, which is undefined).)

geno3141 Jul 10, 2015

11 Online Users

avatar